(untitled) (Experimental biology, 2020)
Fish tagging is a necessary part of many production processes when growing in regulated systems. This article presents the results of research work on tagging sturgeon fish grown in artificial conditions of recirculating aquaculture systems (RAS). The most important advantages of using this method are biological safety, efficiency and non-traumatic. Fish tagging methods are mainly used in the cultivation of sturgeon species (beluga, ship sturgeon, russian sturgeon, siberian sturgeon, sterlet, etc.), which are necessary for many production processes, including: harvesting of producers, selection of fish for spawning companies, breeding work with repair and breeding stock, determination of viability in sturgeon farms. For successful tagging of sturgeon fish, the article presents the most effective places of the studied area and methods of tagging. An example of the correct position of the chip sensor of the passive integrated transponder (PIT mark) when administered with a syringe-injector is presented, as well as the results of alternative methods of tagging sturgeon fish. The optimal location of the workplace during fish tagging is also described. The results of the study are aimed at determining the most effective method of tagging, which contributes to effective and efficient work in the cultivation of sturgeon fish in the RAS.